Surgical treatment in pregnant women with ovarian tumors and tumor-like masses - L. V. Adamyan; K. I. Zhordania; S. A. Martynov; A. Yu. Danilov; A. V. Kozachenko; Z. R. Zurabiani; E. S. Lyashko; A. V. Nikolayeva; Yu. I. Lipatenkova; E. A. Kulabukhova (Опухоли женской репродуктивной системы)
The paper describes the possibilities of new surgical technologies used to treat ovarian tumor and tumor-like masses in pregnant patients. The used surgical treatment contributes to the normal course of pregnancy and the maintenance of reproductive function. Laparoscopic intervention allows timely surgical treatment in a required volume and has no negative impact on the course of pregnancy and fetal and neonatal status.